Yurchenko I.V., Yasynskyy V.K. Stochastic (B,S)-Market under the Action of External Disturbances of the Random Value Type // Modern Scientific Researches.– 2020.– Iss. 13, Part 2.– P. 32–39. - Yurchenko, Igor Valeryjovych; Yasynskyy, Volodymyr Kyryllovych (Published by:Yolnat PE, Minsk, Belarus., 2020)
Stochastic linear models of the value of bonds and shares in the form of linear diffusion stochastic Gikhman-Ito differential equations are investigated. Algorithms for implementing the solutions of these equations are given.
Одержано стохастичні лінійні моделі вартості облігацій та акцій у вигляді ліні йних дифузійних стохастичних диференціальних рівнянь Гіхмана-Іто. Наведено алгоритми реалізації розв’язків цих рівнянь.
Keywords: value model, bond, stock, random variable, stochastic differential equation